Influence of dietary lysine on growth performance of high-lean growth gilts fed from 160 to 300 lb - Friesen, K.G.; Owen, K.Q.; Richert, B.T.; Kats, L.J.; Kerr, B.J.; Nelssen, Jim L.; Goodband, Robert D.; Tokach, Michael D.; Unruh, John A.; Kropf, Donald H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One-hundred eight high-lean growth gilts (159.6 lb) were used to determine the dietary lysine requirement to optimize growth performance from 160 to 300 lb. The experiment was designed as a randomized complete block, with initial weight serving as the blocking factor. Six dietary treatments were used, ranging from .44 to .94% digestible lysine (.59 to 1.16% total lysine). Pigs were housed in pens of three, with six replicate pens/treatment. Pig weights and feed disappearance were collected weekly to calculate average daily gain (ADG), average daily feed intake (ADFI), and feed efficiency (F/G). Average daily gain increased from 160 to 230 lb, from 230 to 300 lb, and from 160 to 300 lb. Average daily feed intake was not influenced by dietary treatment. The gilts consumed 6.47, 6.65, and 6.56 lb/day from 160 to 230, from 230 to 300, and from 160 to 300 lb, respectively. Thus, F/G improved linearly from 160 to 230 lb and quadratically from 230 to 300 and from 160 to 300 lb as a function of increased ADG. Lysine intake was increased linearly for all three weight periods as digestible lysine increased in the diet. The data from this experiment suggest that high-lean growth gilts requires at least 26 g/d of lysine from 160 to 230 and from 230 to 300 lb. Thus, matching nutrition with genetics is essential to optimize both rate and efficiency of gain.
Keywords: Swine; Pigs; Growth; Genotype; Gilts